Pendekatan Pendidikan Anak: Keteladanan, Nasehat dan Perhatian - Siregar, Abu Bakar Adanan (Prodi PIAUD STAI Sumatera Medan, 2021)
In the process of development and efforts to find his identity, it is not uncommon for children to do things that violate the rules of norms, religion and morals. This reality needs to get the attention of all parties, especially in choosing an educational approach to children. This article presents the approach of nudity, advice and attention in education to children. This paper uses a descriptive analysis approach. The conclusion of this article is that: (1). Accuracy is effective for aspects of education aimed at the formation of certain attitudes and skills. (2). The approach of advice can open the children's eyes to the nature of something, and encourage it to go to a noble situation and decorate it with noble character and equip it with Islamic principles. (3). The approach of giving attention khsususnya when the child feels embarrassed, inferior, not even dare to face others, this approach of attention can foster courage, awareness, maturity of his thinking